Investigating The Adoption of Augmented Reality for Vocational Student Engineering Materials in Hybrid Learning - Badriyah, Nurul Lailatul; Yusuf, Munawir; Efendi, Agus (AIBPM Publisher, 2023)
Education in Indonesia has experienced developments related to the use of technology. Learning on personal computers (PC) and smartphone technology devices is common, and it is also referred to as